(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In modern education, the assessment of students’ knowledge, skills, and competencies is no longer merely a process of control or assigning grades. It is increasingly becoming an integral part of the teacher’s didactic and educational strategy. Fair, transparent, and accuracy-focused assessment systems are gaining critical importance in ensuring the quality of education.